2021
DOI: 10.1055/s-0041-1736402
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Magnetic Resonance Parkinsonism Index in Differentiating Progressive Supranuclear Palsy from Parkinson's Disease among South Indian Population: A Retrospective Case Control Study

Abstract: Context Progressive supranuclear palsy (PSP) is a neurodegenerative disorder which comes under Parkinsonism plus syndrome. As this spectrum of disease has many overlapping clinical as well as imaging findings, some quantitative parameters like magnetic resonance Parkinsonism index and midbrain/pons ratio are useful to differentiate PSP from other PD patients. Aims The study aimed to detect sensitivity and specificity of magnetic resonance Parkinsonism index in differentiating PSP from PD. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…After duplicate record elimination, 1096 records were screened by reviewing the title and abstract, eliminating 702 further studies. For the 337 remaining records, full texts were reviewed, eliminating 315 records (unrelated content: n = 280; patient or control group consisting of <10 subjects: n = 22 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]; full text unavailable: n = 1 [38]; non-extractable data: n = 1 [39]; data in median/quartiles: n = 4 [40][41][42][43]; identical study cohorts or study cohorts with significant overlap: n = 2 [8,44]; data on PSP/MSA cohorts without distinction of RS/MSA-P phenotypes: n = 5 [45][46][47][48][49]). Five studies were identified via manual search of related papers, references, and citing papers [13,[50][51][52][53].…”
Section: Literature Search and Screening Resultsmentioning
confidence: 99%
“…After duplicate record elimination, 1096 records were screened by reviewing the title and abstract, eliminating 702 further studies. For the 337 remaining records, full texts were reviewed, eliminating 315 records (unrelated content: n = 280; patient or control group consisting of <10 subjects: n = 22 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]; full text unavailable: n = 1 [38]; non-extractable data: n = 1 [39]; data in median/quartiles: n = 4 [40][41][42][43]; identical study cohorts or study cohorts with significant overlap: n = 2 [8,44]; data on PSP/MSA cohorts without distinction of RS/MSA-P phenotypes: n = 5 [45][46][47][48][49]). Five studies were identified via manual search of related papers, references, and citing papers [13,[50][51][52][53].…”
Section: Literature Search and Screening Resultsmentioning
confidence: 99%